Analisis Break-Even Point Biaya Pendidikan di Universitas untuk Meningkatkan Fasilitas dan Pembelajaran yang Kompetitif: Break-Even Point Analysis of University Education Costs to Enhance Competitive Facilities and Learning Quality - Muslikhin, Muslikhin; Nugraha, Mulyawan Safwandy (Sekolah Tinggi Agama Islam Kharisma Cicurug Sukabumi, 2023)
Higher education institution in Indonesia faces complex challenges in the financial management of institutions. This research analyzes the Break Even Point (BEP) at Al-Ghifari University Bandung City as a strategic basis in the development of competitive facilities and learning. With a descriptive quantitative approach and referring to financial management theory, the Total Approach, Ratio Contribution Margin (RCM), and Margin of Safety (MoS) methods were used to evaluate the balance between income and costs. The results of the analysis over a five-year period showed significant growth in net income and cost management efficiency, indicating the financial resilience and operational efficiency of the university. This research also highlights the positive correlation between understanding BEP and resource allocation policies for facility investment and academic excellence programs. These findings provide an important contribution for universities in designing sustainable financial strategies and promoting quality higher education that is adaptive to competitive dynamics. With proper BEP management, Al-Ghifari University has a great opportunity to improve institutional competitiveness and the overall quality of academic services.